Assessing the impact of abstracts from the Thoracic Society of Australia and New Zealand in Cochrane reviews. - Hopewell, S (2003)
OBJECTIVE: The aim of this study was to assess the potential impact of including trials, reported in conference abstracts from the Thoracic Society of Australia and New Zealand, in Cochrane reviews. METHODOLOGY: Abstracts from the Thoracic Society of Australia and New Zealand, published in the Australian and New Zealand Journal of Medicine (1981-1998), were read to identify all reports of randomized trials. A search was carried out of the Cochrane Database of Systematic Reviews (Issue 1, 2002) for each trial reported in a conference abstract to try to identify Cochrane reviews in which the conference abstract might be eligible for inclusion. If it was unclear, the authors of the review were contacted. RESULTS: A total of 187 reports of randomized trials were identified: 101 (54%) had been published as a full report and 86 (46%) remained unpublished. Thirty-four (72%) were reports of randomized controlled trials and 52 (28%) were quasi-randomized or possibly randomized trials. The total number of patients included in the trials was 9691; range 4-1203 (median 20; IQR 11-47). No possible Cochrane review was found for 145 of the 187 trials reported in the conference abstracts. Possible reviews were identified for 42 trials, 24 of which were already mentioned in Cochrane reviews. For the remaining 18 trials, only three were said to be eligible for inclusion. CONCLUSION: A search of conference abstracts identified a number of reports of randomized trials, potentially eligible for inclusion in reviews of health care. However, the majority of trials were not relevant for inclusion in an existing Cochrane review. This is most likely because there are currently too few reviews to deal with the topics covered in the abstracts.